Evaluating the Hydrochemistry of Geno Hot Spring in Southern Iran - Asadpour, G. (Asian Journal of Chemistry, 2012)
Geno hot spring is located in Hormozgan province in south of Iran where an arid climate dominates. Hydrochemistry of Geno hot spring has been considered within the study. Major anions and cations were measured and the dominant water type was determined as sodium and chloride ions. The abundance of salt domes within the study area may be introduced as the main reason of such water type appearance. Furthermore, gradual decreasing trend of spring flow rate during last decades has also enhanced the salinization process. Due to very high salinity as well as sodium alkali hazard (extreme values of sodium absorption ratio), no agricultural use may be considered for such water. As the main use of water in the study area is contributed to agriculture, implementing modern mechanized irrigation techniques accompanied by planting crops with low water demand and high tolerance against salinity may be recommended.